The impact of prowess practicing of swift marketing: An analytic study in Zain Iraq Telecommunications (Entrepreneurship Journal for Finance and Business, 2021)
Due to the heated competition and the development of modern technology and the importance of the economic aspect, which most sectors center around it, it is the telecommunication sector ,my research aims to address that impact. The impact of the independent variable in marketing prowess as a dependent variable. The research sample was selected at Zain Iraq Telecommunications/Baghdad and the issue was the extent to which agile operations in marketing prowess would be fared in. During the identification, a descriptive exploratory approach was used in SPSS-ver 23data analysis. The research used a series of conclusions, the most important of which was that the company adopts a variety of marketing techniques and techniques that help to attract new customers on an ongoing basis. The research recommended that the company should focus on developing continuous service distribution channels to meet customer demands.